Modelling of the fatigue crack initiation and propagation behaviour in metals and alloys - Ribeiro, Víctor Hugo (2021)
Fatigue is the main causes of mechanical fractures in structural details under cyclic loading. There are several models to describe low-cycle fatigue behavior based on strain damage criteria, such as Coffin-Manson-Morrow, which is used in the crack initiation phase. The Paris law is only applicable in the stable region of crack growth (region II), and, as a consequence of this, several models have emerged derived from it emerged to overcome this limitation, increasing the number of variables and parameters required and, consequently, making the solution costly. Other models such as UniGrow, Huffman, Peeker, among others, describe the initiation and propagation phases of fatigue cracks, adopting the concept of successive crack restarts (increments) based on local approaches. In this research, low-cycle fatigue modeling based on the Huffman approach using strain energy density and considering dislocation density is investigated and discussed. To this end, several methodologies to evaluate low-cycle fatigue resistance based on the Huffman approach and exploring different dislocation density parameters are suggested: (i) critical dislocation density associated with greater strain amplitude; (ii) average value of dislocation density from available experimental fatigue data and, (iii) stochastic Monte Carlo (MC) prediction considering the variability of dislocation density and the cyclic strain hardening coefficient. Experimental fatigue data of Al1050, Al6061-T651 and AlMgSi0.8 alloys from the literature are used in this study. Furthermore, a comparison is made between the experimental fatigue data and the stress-life curves based on the various suggested methodologies. Additionally, a comparison of the effect of various crack closure/opening models on the fatigue crack growth behavior of Al6061-T651 alloy is presented. The crack closure models under consideration are: Elber; Katcher-Kaplan; Clerivet-Bathias; Schijve; Zhang; Newman; Savaidis; Codrington-Kotosov; and Correia. A comparison between these models is done. Furthermore, modeling of the fatigue crack growth behavior for the Al6061-T651 alloy was suggested using the Huffman model based on the strain energy density of the dislocations considering the effects of residual stresses ahead of the crack tip(x), where these stresses are related to the fatigue damage of a crack increment ∆a, as a calibrator parameter. Two approaches suggested by Noroozi and Huffman are studied and discussed. In modeling fatigue crack growth behavior, the influence of the calculated strain energy density for the critical dislocation density values associated with the largest strain amplitude and the average dislocation density value for available experimental fatigue results were also considered in this investigation. The dislocation density values studied do not significantly influenced the fatigue crack propagation behavior. It is also concluded that the procedure for considering the effects of residual stresses influences the calibrator, ∆a, and it is not possible to conclude which is the best method to describe the effects of residual stresses.